Boosting disassembly of π–π stacked supramolecular nanodrugs under tumor microenvironment by introducing stimuli‐responsive drug‐mates - Wenzhe Xu; Ruixu Yang; Yingke Xue; Yang Chen; Shuwei Liu; Songling Zhang; Yonggang Wang; Yi Liu; Hao Zhang (Aggregate)
Abstract Numerous reports have demonstrated the construction of supramolecular nanodrugs (SNDs) via the π–π stacking of drug molecules for antitumor applications because most drugs possess aromatic rings or other planar conjugate units. However, the destruction of π–π stacking and the subsequent disassembly of SNDs under tumor microenvironment (TME), which is the precondition for drug release, have not been clearly described. In this work, based on a disassembly model of π–π stacked naphthoquinone SNDs, the influence of co‐assembled drugs on disassembly is delineated. Both the experimental observation and computational simulation indicate that the disassembly of SNDs under simulated TME highly depends on the disassembly activation energy (ΔEdis) of neighboring π–π stacked molecules. Owing to the high ΔEdis, the disassembly of self‐assembled naphthoquinone SNDs is greatly restricted. Meaningfully, the ΔEdis is the sum of a series of activation energy according to the specific stimuli of TME. Thus, a concept of stimuli‐responsive drug‐mates is proposed for boosting the disassembly of π–π stacked SNDs, namely the foremost co‐assembly of π‐conjugated drugs with additional drug molecules that possess relatively weak π–π interaction but high TME responsiveness. Further computational simulation reveals that the introduction of stimuli‐responsive drug‐mates significantly lowers the ΔEdis, thus accelerating the disassembly of SNDs and the release of drug payloads. Holding the advantages of π‐conjugated drug library, the concept of stimuli‐responsive drug‐mates gives an extensive design of π–π stacked SNDs toward heterogeneous nidus microenvironment responsiveness, which highlights the superiority of widely used drug co‐assembly strategy in constructing multifunctional SNDs.